2019
DOI: 10.1002/rcm.8480
|View full text |Cite
|
Sign up to set email alerts
|

A four‐step filtering strategy based on ultra‐high‐performance liquid chromatography coupled to quadrupole‐time‐of‐flight tandem mass spectrometry for comprehensive profiling the major chemical constituents of Akebiae Fructus

Abstract: Rationale Akebiae Fructus (AF) is a traditional Chinese medicine (TCM) with antiphlogistic, analgesic, antineoplastic, diuretic, antirheumatic, antidepressant and antiobesity activities. Identification of chemical constituents from AF is helpful to discover the potential active ingredients and to control its quality. Methods The four‐step filtering strategy was as follows: (1) To extract the accurate mass by the different adduct ions. (2) To screen different types of the compounds using diagnostic ions. (3) By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Because of the complexity of these components, their comprehensive analysis was extremely difficult. Since the mid‐2000s, because of its high separation resolution, enhanced separation speed, unmatched sensitivity, and minimal sample preparation, liquid chromatography/mass spectrometry (LC/MS) has been increasingly used in natural products research . In addition, the low sample quantity requirement makes LC/MS even more attractive to TCM scientists.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complexity of these components, their comprehensive analysis was extremely difficult. Since the mid‐2000s, because of its high separation resolution, enhanced separation speed, unmatched sensitivity, and minimal sample preparation, liquid chromatography/mass spectrometry (LC/MS) has been increasingly used in natural products research . In addition, the low sample quantity requirement makes LC/MS even more attractive to TCM scientists.…”
Section: Introductionmentioning
confidence: 99%
“…NL means that the compounds of the same or similar structure lose the same neutral fragment under the same mass conditions. NLs are essential for screening substances . The combination of CF and NLs can achieve the efficient screening of chemical components in TCMs.…”
Section: Introductionmentioning
confidence: 99%
“…NLs are essential for screening substances. [14][15][16] The combination of CF and NLs can achieve the efficient screening of chemical components in TCMs.…”
mentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic autoimmune and inflammatory disease that can cause pain, disability and premature death. It is reported that RA could be treated and controlled effectively using antirheumatic HDSs . With the growing interest in the development of antirheumatic HDSs, the quality control of these drugs is a challenging task, especially detection of synthetic antirheumatic drugs in HDSs …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that RA could be treated and controlled effectively using antirheumatic HDSs. [4][5][6] With the growing interest in the development of antirheumatic HDSs, the quality control of these drugs is a challenging task, especially detection of synthetic antirheumatic drugs in HDSs. 1,4 Various analytical techniques based on chromatography, spectroscopy, bioassays, mass spectrometry, capillary electrophoresis, and other successful methods have been used for determination of synthetic drugs in adulterated HDSs.…”
Section: Introductionmentioning
confidence: 99%